Assessment of foot posture and related factors in patients with knee osteoarthritis - Mazlum Serdar AKALTUN; Burhan Fatih KOÇYİĞİT (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to compare foot posture between patient and control groups, and to identify factors associated with foot posture abnormality in knee osteoarthritis (OA). Patients and methods: This case-control study included a total of 115 patients (26 males, 89 females; mean age: 54.4±9.3 years; range, 29 to 73 years) with OA and 77 healthy controls (20 males, 57 females; mean age: 52.1±8.1 years; range, 32 to 69 years) between May 2019 and July 2019. The participants were evaluated using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Visual Analog Scale (VAS), and the Beighton criteria. Radiological assessments were performed using the Kellgren-Lawrence grading, condylar plateau angle, and medial tibiofemoral joint width. The Foot Posture Index-6 (FPI-6) was used for foot posture analysis and three groups were formed as supinated, neutral, and pronated postures. Results: Foot posture was significantly different between the patient and control groups (p<0.05). Of the patients with knee OA, significant differences were found in the VAS, WOMAC-pain, WOMAC-physical function, and WOMAC-total (p<0.05) among the foot postures. No significant difference was found among the foot posture groups in terms of the radiological parameters and WOMAC-stiffness (p>0.05). Hypermobility and WOMAC-total scores were significantly associated with foot posture abnormality (p<0.05). Conclusion: Joint hypermobility and foot posture are the factors which may influence the clinical characteristics of knee OA. Foot posture and joint hypermobility should be taken into consideration during the examination and management of patients with knee OA.